Transhumanism, Nietzsche and Politics: A Commentary on Their Relationship - Markopoulou, Anna Ch. (Journal of Posthumanism, 2021)
The aim of this commentary is to highlight the relationship between Nietzsche and Transhumanism on the occasion of the publication of the Posthuman Studies Reader in 2021, which is edited by Evi D. Sampanikou and Jan Stasienko. More specifically, this commentary focuses on the fact that the Reader promotes Nietzsche as the official forerunner of Transhumanism, since it places humans at a transition point between animal and Overhuman.The analysis of the ten transhumanist texts in the Reader shows that, in essence, Transhumanism is not a transition but an overcoming of the human and, from this point of view, it is not in line with Nietzsche's conception. Moreover, this commentary focuses on the relationship between Transhumanism and politics and shows that the political dimension is entirely absent from most of the Transhumanist texts in the Reader. Thus, transhumanism should re-evaluate its epistemological foundations and its relation to politics.